Translation and Psychometric Properties of the Persian Version of Patients' Perceptions of Safety Culture Scale in the Hospital Setting - Seyed javad Hosseini; Monir Ramezani; Jamshid Jamali; Abbas Heydari (Patient Safety and Quality Improvement Journal, 2023)
Introduction:Patient safety culture (PSC) was considered an essential predictor of healthcare quality. Measurement of PSC required a valid and reliable scale. So, the current study aimed to determine the validity and reliability of patients' perceptions of safety culture scale (PPSCS) in the context of Iran.Materials and Methods: This study was a scale psychometric assessment in the Iran context. Current study had three phases: preparation, translation and psychometric evaluation. Scale translation was performed based on the forward-backward framework. Face and content validity, test-retest reliability, and internal consistency were evaluated. Also, corrected item-total correlation for each item was reported based on data collection from 119 patients admitted to Esfarayen Imam Khomeini hospital. Analysis was done in SPSS V.16.Results: Content validity ratio (CVR) and content validity index (CVI) were between 0.8 to 1. Also, corrected item-total correlation was between 0.604 and 0.864. Intra correlation coefficient (ICC) and alfa Cronbach were 0.974 and 0.939, respectively.Conclusion: Results showed PPSCS had acceptable validity and reliability in the Iran context. This scale can apply in different studies to measure patients' perceptions of safety culture in different hospital settings.